1996
DOI: 10.1002/j.1460-2075.1996.tb01076.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenesis of a stacking contact in the MS2 coat protein-RNA complex.

Abstract: The thermodynamic contribution of a stacking interaction between Tyr85 in MS2 coat protein and a single‐stranded pyrimidine in its RNA binding site has been examined. Mutation of Tyr85 to Phe, His, Cys, Ser and Ala decreased the RNA affinity by 1–3 kcal/mol under standard binding conditions. Since the Phe, His and Cys 85 proteins formed UV photocrosslinks with iodouracil‐containing RNA at the same rate as the wild‐type protein, the mutant proteins interact with RNA in a similar manner. The pH dependence of KD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 35 publications
5
39
1
Order By: Relevance
“…3, 8). Analogous data have been reported with certain other complexes: For example, alanine substitution of a stacking tyrosine in the MS2 coat protein-RNA complex reduces binding 160-fold, while substitution of a phenylalanine in the U1A-RNA complex is reported to reduce binding 10,000-fold (LeCuyer et al 1996;Nolan et al 1999). We suggest that the abundance of consecutive stacking interactions in the FBF-2-RNA complex mitigates the effects of single mutations, and local plasticity allows substitutions of stacking side chains with reduced effect on binding affinity.…”
Section: Discussionsupporting
confidence: 73%
“…3, 8). Analogous data have been reported with certain other complexes: For example, alanine substitution of a stacking tyrosine in the MS2 coat protein-RNA complex reduces binding 160-fold, while substitution of a phenylalanine in the U1A-RNA complex is reported to reduce binding 10,000-fold (LeCuyer et al 1996;Nolan et al 1999). We suggest that the abundance of consecutive stacking interactions in the FBF-2-RNA complex mitigates the effects of single mutations, and local plasticity allows substitutions of stacking side chains with reduced effect on binding affinity.…”
Section: Discussionsupporting
confidence: 73%
“…We found that Tyr at position 122 in M.CviBIII is the site of modification in the photo-cross-linking reaction. Very high photo-cross-linking yields were also reported for the RNA-binding domain of the U1A spliceosomal protein (20) and the bacteriophage MS2 coat protein (21), where three-dimensional structures of the protein-RNA complexes are known (34,35). In these complexes a Tyr residue is found in a -stacking arrangement with a cytosine residue, and replacement of these cytosine residues by 5-iodouracil resulted in 67-90% photo-cross-linking yields.…”
Section: Dna Binding Andmentioning
confidence: 86%
“…In this scenario, the stacking interaction between the DNA base and the Tyr836 may be beneficial for the geometry rather than energy barrier for the DNA base movement across the oscillating BH to determine the frequency of forward translocation. The energetic contribution of the RNA base-Tyr stacking interaction has been experimentally calculated as ∼2-5 k B T at room temperature (19,20), supporting this view.…”
mentioning
confidence: 60%